Association between the IL-6 polymorphisms and coal workers' pneumoconiosis in a Chinese Hui population. (14th September 2022) - Xu, Xiangzhao; Yin, Jun; Zhang, Junlong; Xu, Shulan; Yang, Yaowen; Hai, Xiaoyu; Yu, Yongsheng; Lu, Ruirui; Liu, Mingzhou
Objective: To determine whether polymorphisms in IL-6 and IL-12 contribute to the etiology of coal workers' pneumoconiosis (CWP) in a Chinese Hui population, and to evaluate the efficacy and safety of high frequency oscillatory ventilation (HFOV) in the treatment of CWP. Introduction: Genes and the environments interplay in the development of CWP, and the association between the potential functional polymorphisms in many genes and CWP have been reported. Methods: We genotyped the IL-6-634C/G (rs1800796) and IL-12B-1188A/C (rs3212227) polymorphisms in a case-control study including 160 CWP patients and 150 dust-exposed control subjects of Chinese Hui population, and analyzed the associations between these genetic variants and CWP risk. We also evaluated the efficacy and safety of HFOV for whole lung lavage (WLL) in the treatment of CWP. Results: Carrying the C allele of IL-6-634C/G (rs1800796) was associated with decreased risk of CWP ( p < 0.05). No significant differences in allele or genotype frequencies of IL-12B-1188A/C was found between the CWP cases and control subjects ( p > 0.05). Compared with CWP patients with routine WLL, CWP patients received HFOV showed better pulmonary functions. HFOV treatment also yield a significant higher efficient rate (97.50%) than WLL treatment (81.25%, p = 0.001). CWP patients receiving HFOV and WLL treatment both showed significantly increased serum contents of Clara cell protein 16 (CC16) and superoxide dismutase (SOD), and decreased serum contents of serum malonaldehyde (MDA). While the increasing of CC16 and SOD, and decreasing of MDA in patients receiving HFOV was more noticeable than patients receiving WLL. Conclusions: Taking together, the −634C/G polymorphisms in IL-6 play a role in the etiology of CWP. HFOV, when applied in CWP patients, significant improves their pulmonary functions.